Kebijakan Pesantren dalam Pembentukan Karakter PelajarRahmatan Lil ‘Alamin di Era Digitalisasi - Muhamad Jihad Al Haqiqi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
The policy made by Islamic boarding schools is to instill character in students. Research on the strength of the policy makes the students at the boarding school feel that the attitude, mentality and soul of a leader is formed within them. Through rapid digital developments, the structure of cottage life has increasingly changed from the past to the present. The results of this research are a special picture in the community's assessment of the success of the peasantren cottage in producing generations. The many diverse challenges in each era have become an appeal and vigilance in the ongoing education and teaching in Islamic boarding schools. The author's hope is that this view can bring benefits and benefits to all of us.